2020
DOI: 10.1039/d0gc00137f
|View full text |Cite
|
Sign up to set email alerts
|

Trihaloisocyanuric acids in ethanol: an eco-friendly system for the regioselective halogenation of imidazo-heteroarenes

Abstract: Herein, we describe an efficient, rapid and benign protocol for the direct C(sp2)–H bond halogenation (Cl, Br, I) of 2-arylimidazo[1,2-a]pyridines using trihaloisocyanuric acids in ethanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 57 publications
(20 citation statements)
references
References 90 publications
0
19
0
1
Order By: Relevance
“…[ 9 ] Therefore, it is noteworthy to mention that the synthesis and functionalization of IP have received considerable attention from the scientific community . [ 10–13 ] It has been shown that the chemotherapeutic effect of imidazopyridine derivatives can occur via targeting protein kinases. The biological evaluation showed that imidazodipyridine suppresses oncogenic extracellular signal‐regulated kinase (ERK), causing inhibition of human prostate cancer cell DU‐145 proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 ] Therefore, it is noteworthy to mention that the synthesis and functionalization of IP have received considerable attention from the scientific community . [ 10–13 ] It has been shown that the chemotherapeutic effect of imidazopyridine derivatives can occur via targeting protein kinases. The biological evaluation showed that imidazodipyridine suppresses oncogenic extracellular signal‐regulated kinase (ERK), causing inhibition of human prostate cancer cell DU‐145 proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] Over the last decade, great achievements have been made on the direct C—H functionalization of imidazo[1,2‐ a ]pyridines. [ 6 ] For instance, the direct amination, [ 7 ] trifluoromethylation, [ 8 ] alkoxylation, [ 9 ] sulfenylation, [ 10 ] selenylation, [ 11 ] and halogenation [ 12 ] have been realized in the past few years. Nowadays, the simple and sustainable production of more structurally diverse C‐3 functionalized imidazo[1,2‐ a ]pyridines is still significantly and enthusiastically pursued.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…[hmim]Br DCDPH,NBS Chiral Organocatalyst [56] K 2 S 2 O 8 TBAX or NXS [85] (Cl/Br/I) Electrochemical [74] Acyl chloride [91] NXS (X=Br/Cl/I) AlCl 3 /NXS PIDA (X=Br/Cl) NIS,TFA [46] ArI(OAc) 2 [43] PIDA/NaX [76] (X=Cl/Br/I) NaX NFSI [92] (X=Br/I) NaI,Electrolysis [101] TBAB or TBAC [52] (Pummerer) Erythrosin B, NBS,LED [22] PhI(OAc) 2 or K 2 S 2 O 8 NaBr [38] TXCA [102] ChemistrySelect material in case of mono C-5 halogenation in presence of TEMPO possibly indicated that the NXS was being captured by TEMPO preventing subsequent halogenation. N-flurobenzenesulfonimide (NFSI) was used as an oxidant and sodium salts of halogens (bromine and iodine) acted as halogen source for the halogenation of quinolines (137)and arenes.…”
Section: General Halogenation On Heteroarene Systems Using Different ...mentioning
confidence: 99%